EXPERIMENTAL ANALYSIS OF HEAT RECOVERY WHEEL FOR TROPICAL CLIMATE - Rachman, Arfidian; Yuana Dewi Rachman, Arfita; Effendi, Asnal; Nesti, Lisa (Jurnal Teknologi dan Vokasi, 2024)
This paper presented and used experimental analysis to examine design that integrates an active heat recovery wheel mechanism into a windcatcher. A rotational thermal heat recovery is incorporated into the windcatcher channel of the proposed system. An experiment was conducted to examine how the heat recovery mechanism affected the windcatcher performance, demonstrating the system ability to provide the necessary fresh air rates. A test room model, measuring 4x4x3 meters and depicting a small classroom, was integrated with the windcatcher model. Ventilation rates managed to supply sufficient ventilation even with the rotational heat recovery wheel blocked. This active recovery has the potential to lessen the demand on space heating systems in addition to providing enough ventilation. The heat in the exhaust airstreams was caught and transferred to the incoming airstream, boosting the temperature between 7-9oC depending on the indoor/outdoor conditions. This indicates that there is a great deal of room for further development of the idea, allowing for larger-scale testing and investigation of the system's heat transfer characteristics.